Distribution of CFTR mutations in the Czech population: positive impact of integrated clinical and laboratory expertise, detection of novel/de novo alleles and relevance for related/derived populations - Křenková, Petra; Piskáčková, Tereza; Holubová, Andrea; Balaščaková, Miroslava; Krulišová, Veronika; Čamajová, Jana; Turnovec, Marek; Libik, Malgorzata; Norambuena, Patricia; Štambergová, Alexandra; Dvořáková, Lenka; Skalická, Veronika; et al. (Journal of cystic fibrosis, 2013)
BACKGROUND: This two decade long study presents a comprehensive overview of the CFTR mutation distribution in a representative cohort of 600 Czech CF patients derived from all regions of the Czech Republic. METHODS: We examined the most common CF-causing mutations using the Elucigene CF-EU2v1™ assay, followed by MLPA, mutation scanning and/or sequencing of the entire CFTR coding region and splice site junctions. RESULTS: We identified 99.5% of all mutations (1194/1200 CFTR alleles) in the Czech CF population. Altogether 91 different CFTR mutations, of which 20 were novel, were detected. One case of de novo mutation and a novel polymorphism was revealed. CONCLUSION: The commercial assay achieved 90.7%, the MLPA added 1.0% and sequencing increased the detection rate by 7.8%. These comprehensive data provide a basis for the improvement of CF DNA diagnostics and/or newborn screening in our country. In addition, they are relevant to related Central European populations with lower mutation detection rates, as well as to the sizeable North American "Bohemian diaspora".
Keywords: Austrian/Austria; alely; Cystic Fibrosis Transmembrane Conductance Regulator; multiplex ligation-dependent probe amplification; PL; newborn screening; Alleles; USA; Newborn screening; CE; German/Germany; UK; Česká republika; SK; cystic fibrosis transmembrane conductance regulator gene; mužské pohlaví; MLPA; mutace; Polish/Poland; Czech Republic; Hungarian/Hungary; Cystic fibrosis; dítě; Cystic Fibrosis; De novo CFTR mutation; Child; Child, Preschool; DE; Mutation; protein CFTR; Humans; předškolní dítě; Slovak/Slovakia; HU; Clinical Laboratory Techniques; NBS; United States of America; CF; CZ; United Kingdom; Central Europe; klinické laboratorní techniky; Czech Republic/Czech; AT; lidé; Male; CFTR